Running Ahead - Understanding the possibilities and Challenges of Belonging and Identity through the Nimble-Footed Joburg Runner in Times of Precarity - Nyarhi, Thelma (School of African and GenderStuds, Anth and Ling, 2024)
This research reviews the possibilities for livelihoods to emerge through the acts of ‘trying'. It centers itself in the Johannesburg CBD and shares stories of Zimbabwean migrants residing within the metropolis. These stories were collated through the Joburg runners (who consist of female migrants who take it upon themselves to shop, pack, and source transport for their client's consumables). Additional respondents were sought through the runner network systems which included wrappers, and transporters. Literature has largely focused on male migrants. However, the trend of feminized migration continues to rise. This invites the telling of stories of the lived experiences of these women in a place where they are considered as vulnerable ‘soft targets'. Hence the present study traces the nimble footedness of the female migrant in knowing when to cross, recross and crisscross borders and boundaries. The research contributes an added perspective to conventional themigration narrative, within which women are frequently portrayed as the inaudible voices and passive actors and frequently appear as accompanying social actors who moved to join their spouses or merely remain at home and await remittances. Through the prism of the Joburg runners as female migrants, this study invites conversations around (im)mobility, reimagination of belonging and identity. Consequently, what emerged were conversations around borders and boundaries, fear, friendship, familyhood, motherhood, conflict, suffering, trauma, belonging, identity, endurance, and tactical thinking. As wives, mothers, and daughters, with fascinating nimbleness, the Joburg runners always found ways to navigate social boundaries and physical borders in the quest of securing livelihoods for their families. This required the application of kungwara (being clever and calculating) in carrying out their work as Joburg runners. This was no easy task and required the acceptance of incompleteness thereby enabling the openness to social encounters. The conceptual framework employed was one of ‘trying' (kuzamazama) and incompleteness (Nyamnjoh, 2015) which challenges the idea of boundedness and fixity in being, becoming and belonging in contexts where multiple encounters generate myriad interconnections and interdependencies. These encounters through conviviality contest the ideas of rigid prescriptiveness and binary oppositions and enable the migrant to go about their livelihood operations in pragmatic and accommodative ways. Social networks are birthed and result in social cohesion and community building which reimagines the ways of existence, resistance, and endurance through an open disposition to sociality.